MEKANISME SEKOLAH DALAM PENGEMBANGAN KURIKULUM PAI PADA KURIKULUM MERDEKA - Muhammad Syaroni; Muhammad Subhan; Abdul Halim (Fakultas Agama Islam Universitas Billfath, 2024)
The purpose of this research are expected to provide a comprehensive and well-organized overview of the school mechanism in developing the PAI curriculum within the Kurikulum Merdeka.. The object of this research is SMP Simajaya, located in Siman Sekaran, Lamongan. Data collection methods include interviews, observations, and documentation. Based on the analysis and discussion of the data obtained by the researcher, it can be concluded that the development of the PAI curriculum within the Kurikulum Merdeka at SMP Simanjaya is carried out through the formation of a Curriculum Development Team by the school principal, established no later than one month before the start of the new academic year. The team consists of school structural officials, subject teachers, school supervisors, curriculum experts, and the school committee. The team formulate the curriculum components together. The planning process for the implementation of the Kurikulum Merdeka (IKM), which includes the PAI curriculum, begins with drafting the KOSP document, followed by the preparation of the Learning Objective Flow, and then the development of teaching modules and Project Modules for Strengthening the Pancasila Student Profile. The planning is outlined in the SMP Simanjaya Curriculum Document, which includes an analysis of the characteristics of SMP Simanjaya, the school's vision, mission, and objectives, as well as the organization of learning activities.